Enablers and barriers to the construction of motives for learning at the university: The student’s perspective - Jorge Miranda-Ossandón; Andrea Precht; Constanza Lobos; Jorge Valenzuela; Carla Muñoz; Milenko Del Valle (Institute of Advanced Engineering and Science, 2023)
The massification of higher education and the migration to online formats imply changes that affect the ways that people learn and their motivation for learning. In this sense, the motivational orientation of the student can make a difference in learning. This article aims to describe the enablers and barriers to students’ motivation for learning from the perspective of Chilean University students in the areas of health and education. The study was conducted through virtual group interviews. The analysis was carried out on the participants’ accounts from a constructivist approach to grounded theory. The results showed a valuation of the practical and altruistic motives as a structuring motivational axis. In line with the self-determination theory, the existence of a protected space in the classroom appears as an essential motivational enabler of learning, and virtuality is a critical motivational barrier.